The Effectiveness of Canva Media on Data Representation Skills Mathematics Learning in Elementary School - Fernanda, Alfina Mutiara Diaz; Setyaningsih, Nining Setyaningsih; Pramesta, Aulia Luthfi Dewi; Suranti, Popi Suranti; Murtiyasa, Budi Murtiyasa (Universitas Negeri Makassar, 2026)
This study aimed to determine the effectiveness of Canva digital media in improving data representation skills among elementary school students in mathematics learning. Employing a quantitative approach with a one-group pretest–posttest design, the research involved 25 fifth-grade students at SDN Wonokerto 1. Data were collected through a written test measuring students' ability to represent and interpret data in various graphical forms. The data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and the Wilcoxon Signed Rank Test. The results revealed a statistically significant increase in students' scores from pretest (M = 45.20) to posttest (M = 66.00), with a significance value of 0.000 (p < 0.05). These findings confirm that the integration of Canva as a visual-digital learning medium significantly enhances students' data representation skills. Thus, Canva can be recommended as an effective alternative instructional tool to support the development of data literacy and numeracy in elementary mathematics education.